2019
DOI: 10.21203/rs.2.10165/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intern preparedness for the CanMEDS roles and the Dunning-Kruger effect: a survey

Abstract: Background The purpose of this study was to determine whether the first cohort of graduates from a new undergraduate medical programme in Botswana were adequately prepared for internship. Methods The authors surveyed 27 interns and 13 intern supervisors on site, who rated intern preparedness for 44 tasks using a previously validated instrument. Tasks were grouped according to the seven roles of the physician in the CanMEDS framework and Cronbach α values confirmed internal consistency. To determine the directi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There were a further 10 studies including literature reviews, commentaries, and editorials (Table 1). Study participants included final‐year medical students, 6‐25 junior doctors early in their first postgraduate year, 3,13,14,16‐19,26‐42 junior doctors late in internship (>6 months) or in postgraduate year 2 or above 2,14,16,22,24,35,38,42‐57 (Table 1). Twenty‐one studies incorporated feedback or reports from clinical supervisors or training managers 5,7,13,14,17‐19,22,25,31,35,36,39,43,45,55,58‐61 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were a further 10 studies including literature reviews, commentaries, and editorials (Table 1). Study participants included final‐year medical students, 6‐25 junior doctors early in their first postgraduate year, 3,13,14,16‐19,26‐42 junior doctors late in internship (>6 months) or in postgraduate year 2 or above 2,14,16,22,24,35,38,42‐57 (Table 1). Twenty‐one studies incorporated feedback or reports from clinical supervisors or training managers 5,7,13,14,17‐19,22,25,31,35,36,39,43,45,55,58‐61 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…An audit of workplace‐based assessments in South Australia demonstrated that supervisors rated interns at or above “competent/well prepared,” whereas graduates rated themselves more harshly 45 . In contrast, supervisor ratings of intern preparedness were lower compared to interns' self‐ratings in Scotland 43 and Botswana 42 . Several sources reported a lack of graduate preparedness for prescribing 8,15,18 ; however, only one study objectively measured prescribing competencies using a “safe prescribing” assessment 18 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations